The Influence of Problem-Based Learning Model, Expository Learning Model, and Students’ Learning Styles on Their Descriptive Writing Skill - Noflin Merlina Wenas; Golda Juliet Tulung; Audi Yundayani (LPPM Politeknik Saint Paul Sorong, 2022)
Writing is one of the essential skills of language. It is a way we can communicate with others. It is considered a skill that needs study and practice. Although writing is important, many students who are learning English assume that writing is a difficult skill because of some elements that need to be considered, such as word choices, grammar, punctuation, spelling, coherence, and many others. Similarly, the use of monotonous learning models by teachers without regard to the student's learning style. The aim of the research was to analyze the influence of the PBL model, the EL model, and students’ learning styles on their descriptive writing skills. This research used a quasi-experimental research design with a pattern of treatment by the level design. The population in this study was all class VII students at SMP Advent 3 Ranotana as many as 23 students (11 women and 12 men) aged 11-12 years in experimental classes who received treatment in the form of PBL learning models and in control classes involving 21 students (8 women and 13 men) using EL model. From the data analysis, it was found that there was no significant difference between the PBL model, and EL model. The learning model has no effect on the student’s descriptive writing skills. There is a significant difference between visual, auditory, and kinesthetic learning styles. In this case, learning styles have an effect on the student’s descriptive writing skills. However, the interaction between learning models and styles affects the student's descriptive writing skills